Novel nano coating refractory castable and preparation method thereof
By adopting new nano-coated refractory castables and using raw materials such as modified nano hollow cage-shaped carbon microspheres, the shortcomings of existing refractory castables in high temperature stability, thermal shock resistance and mechanical strength are solved, and higher refractory performance is achieved.
Patent Information
- Application Number
- CN202510220918.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The existing refractory castables have poor performance in high temperature stability, thermal shock resistance and mechanical strength, and cannot meet the high requirements for the performance of refractory materials in the market.
New nano-coated refractory castables are used to improve the thermal conductivity and pore structure of the material through the preparation method of modified nano-hollow cage carbon microspheres, nano boron nitride, nano-titanium dioxide, nano-boron carbide, zirconium oxide, cesium garnet powder, lanthanum oxide, binding agent and water reducer.
The high temperature stability, thermal shock resistance and mechanical strength of refractory castables are significantly improved, and can better meet the high requirements of the market for the performance of refractory materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a novel nano-coated refractory castable and a preparation method thereof. Background Art
[0002] There are two types of refractory materials, namely shaped refractory materials and unshaped refractory materials. Among them, shaped refractory materials generally refer to refractory bricks, which have standard shapes and can also be temporarily processed when building and cutting according to needs. They are finished materials that can be directly installed.
[0003] Unshaped refractory materials, also called castables, are a mixture of refractory aggregates, powders and binders. They need to be mixed with water or other liquids before use, and have strong fluidity. Refractory castables have been rapidly developed around the world due to their simple production process, low cost, convenient application, wide application range, easy construction, on-site preparation, good integrity and good use effect.
[0004] Refractory materials are also widely used in fixed / movable chutes, ladles, tundishes and other parts of non-ferrous smelting. Practical results show that these parts have put forward higher requirements on the performance of refractory materials, that is, refractory materials must have "strong isolation", "non-copper", "high strength", "corrosion resistance", "thermal shock resistance", "non-toxic", "quick repair", "easy to clean" and other properties to meet market demand. However, due to the unreasonable matching of raw material particles and other problems, the existing refractory castables have poor high temperature stability, low strength, easy cracking and other problems that cannot meet the market demand. Based on this, it is urgent to provide a new refractory castable to improve the high temperature stability, thermal shock stability and mechanical strength of the refractory castable. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the primary purpose of the present invention is to provide a novel nano-coated refractory castable having excellent high temperature stability, thermal shock resistance and mechanical strength.
[0006] Another object of the present invention is to provide a method for preparing a novel nano-coated refractory castable, which is simple and easy to operate.
[0007] The purpose of the present invention is achieved through the following technical solutions: A novel nano-coated refractory castable comprises the following raw materials by weight: 5-10 parts of magnesium oxide, 50-70 parts of modified nano hollow cage carbon microspheres, 5-10 parts of nano boron nitride, 1-3 parts of nano titanium dioxide, 10-20 parts of nano boron carbide, 5-10 parts of zirconium oxide, 0.5-1 parts of cesium garnet powder, 0.5-1 parts of lanthanum oxide, 0.5-1 parts of binder, and 0.1-0.3 parts of water reducer; The preparation process of the modified nano hollow cage-like carbon microspheres is as follows: The nano hollow cage-like carbon microspheres, silicon powder, diatomaceous earth, calcium stearate and water are uniformly mixed and granulated, and the modified hollow cage-like carbon microspheres are obtained after drying and calcining.
[0008] Furthermore, the mass ratio of the nano hollow cage-like carbon microspheres, silicon powder, diatomaceous earth, calcium stearate and water is 1:(2-4):(1-3):(0.5-1.5):(12-18).
[0009] Furthermore, the drying temperature is 55-65° C., and the drying time is 20-22 hours.
[0010] Furthermore, the calcination temperature is 900-1000° C., and the calcination time is 25-35 min.
[0011] Furthermore, the particle size of the cesium garnet powder is 50-70 μm.
[0012] Furthermore, the binder is aluminate cement, and the water reducing agent is sodium tripolyphosphate.
[0013] Furthermore, the content of aluminum oxide in the aluminate cement is 50-80wt%.
[0014] Furthermore, the particle size of the nano boron nitride is 20-40 nm, the particle size of the nano titanium dioxide is 50-100 nm, and the particle size of the nano boron carbide is 30-50 nm.
[0015] The preparation method of the novel nano-coated refractory castable comprises the following steps: Weigh each raw material according to the weight ratio and mix them evenly.
[0016] The present invention has the following effects compared with the prior art: 1. The refractory castable of the present invention includes raw materials such as modified nano hollow cage-like carbon microspheres and cesium garnet powder. The modified nano hollow cage-like carbon microspheres are obtained by modifying the nano hollow cage-like carbon microspheres with silicon powder, diatomaceous earth, and calcium stearate. The thermal conductivity of the nano hollow cage-like carbon microspheres is further enhanced after the modification, thereby improving the high temperature stability of the castable; furthermore, the pore structure of the nano hollow cage-like carbon microspheres is improved after the modification, and has excellent toughness, and can absorb and release the stress at the crack tip when the temperature changes, which helps to reduce the material cracking caused by the concentration of thermal stress, thereby improving the thermal shock resistance of the refractory castable. In addition, silicon carbide is formed on the surface of the nano hollow cage-like carbon microspheres during the calcination process, which further improves the high temperature stability and overall thermal shock resistance of the refractory castable. The cesium garnet powder itself has a strong hardness, and the synergistic effect with the modified carbon microspheres further improves the strength characteristics of the castable.
[0017] 2. The refractory castable of the present invention also includes nano raw materials such as nano boron nitride, nano boron carbide and nano boron carbide, which have good film-forming properties and are helpful for preparing nano-coated refractory castables.
[0018] 3. The refractory castable of the present invention has excellent high temperature stability, thermal shock resistance and mechanical strength. DETAILED DESCRIPTION
[0019] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0020] The nano hollow cage-shaped carbon microspheres involved in the invention have an outer diameter of 310-350nm, an inner diameter of 230-255nm, and a mesopore diameter of 30-38nm; the particle size of the cesium garnet powder is 50-70μm; the particle size of the nano boron nitride is 20-40nm, the particle size of the nano titanium dioxide is 50-100nm, the particle size of the nano boron carbide is 30-50nm, and the particle size of the carbon powder is 10μm.
[0021] 1. Preparation Example Preparation Example 1 Preparation Example 1 provides a modified nano hollow cage-shaped carbon microsphere, and the specific preparation method is as follows: According to the mass ratio of nano hollow cage-like carbon microspheres, silicon micropowder, diatomaceous earth, calcium stearate and water of 1:3:2:1:15, nano hollow cage-like carbon microspheres, silicon micropowder, diatomaceous earth, calcium stearate and water are evenly mixed and granulated, dried at 60°C for 21 hours, and then calcined at 950°C for 30 minutes to obtain modified hollow cage-like carbon microspheres.
[0022] Preparation Example 2 Preparation Example 2 provides a modified nano hollow cage-like carbon microsphere, and the specific preparation method is as follows: According to the mass ratio of nano hollow cage-like carbon microspheres, silicon micropowder, diatomaceous earth, calcium stearate and water of 1:2:1:0.5:12, nano hollow cage-like carbon microspheres, silicon micropowder, diatomaceous earth, calcium stearate and water are evenly mixed and granulated, dried at 55°C for 22h, and then calcined at 900°C for 35min to obtain modified hollow cage-like carbon microspheres.
[0023] Preparation Example 3 Preparation Example 3 provides a modified nano hollow cage-shaped carbon microsphere, and the specific preparation method is as follows: According to the mass ratio of nano hollow cage-like carbon microspheres, silicon micropowder, diatomaceous earth, calcium stearate and water of 1:4:3:1.5:18, nano hollow cage-like carbon microspheres, silicon micropowder, diatomaceous earth, calcium stearate and water are evenly mixed and granulated, dried at 65°C for 20 hours, and then calcined at 1000°C for 25 minutes to obtain modified hollow cage-like carbon microspheres.
[0024] 2. Example Example 1 Example 1 provides a new type of nano-coated refractory castable, which is composed of the following raw materials in parts by weight: 8 parts of magnesium oxide, 60 parts of modified nano hollow cage-like carbon microspheres obtained in Preparation Example 1, 7 parts of nano boron nitride, 2 parts of nano titanium dioxide, 15 parts of nano boron carbide, 8 parts of zirconium oxide, 0.7 parts of cesium garnet powder, 0.6 parts of lanthanum oxide, 0.6 parts of aluminate cement, and 0.2 parts of sodium tripolyphosphate, wherein the content of alumina in the aluminate cement is 60wt%.
[0025] Example 1 also provides a method for preparing the novel nano-coated refractory castable. The specific preparation process is as follows: Weigh each raw material according to the weight ratio and mix them evenly.
[0026] Example 2 Example 2 provides a new type of nano-coated refractory castable, which is composed of the following raw materials in parts by weight: 5 parts of magnesium oxide, 50 parts of modified nano hollow cage carbon microspheres obtained in Preparation Example 2, 5 parts of nano boron nitride, 1 part of nano titanium dioxide, 10 parts of nano boron carbide, 5 parts of zirconium oxide, 0.5 parts of cesium garnet powder, 0.5 parts of lanthanum oxide, 0.5 parts of aluminate cement, and 0.1 parts of sodium tripolyphosphate, wherein the content of alumina in the aluminate cement is 50wt%.
[0027] Example 2 also provides a method for preparing the novel nano-coated refractory castable. The specific preparation process is as follows: Weigh each raw material according to the weight ratio and mix them evenly.
[0028] Example 3 Example 3 provides a new type of nano-coated refractory castable, which is composed of the following raw materials in parts by weight: 10 parts of magnesium oxide, 70 parts of modified nano hollow cage-like carbon microspheres obtained in Preparation Example 3, 10 parts of nano boron nitride, 3 parts of nano titanium dioxide, 20 parts of nano boron carbide, 10 parts of zirconium oxide, 1 part of cesium garnet powder, 1 part of lanthanum oxide, 1 part of aluminate cement, and 0.3 parts of sodium tripolyphosphate, wherein the content of alumina in the aluminate cement is 80wt%.
[0029] Example 3 also provides a method for preparing the novel nano-coated refractory castable. The specific preparation process is as follows: Weigh each raw material according to the weight ratio and mix them evenly.
[0030] 3. Comparative ratio Comparative Example 1 Comparative Example 1 provides a castable, which is composed of the following raw materials in parts by weight: 8 parts of magnesium oxide, 60 parts of nano hollow cage-like carbon microspheres, 7 parts of nano boron nitride, 2 parts of nano titanium dioxide, 15 parts of nano boron carbide, 8 parts of zirconium oxide, 0.7 parts of cesium garnet powder, 0.6 parts of lanthanum oxide, 0.6 parts of aluminate cement, and 0.2 parts of sodium tripolyphosphate, wherein the content of alumina in the aluminate cement is 60wt%.
[0031] The specific preparation method of the castable in Comparative Example 1 is consistent with that in Example 1.
[0032] Comparative Example 2 Comparative Example 2 provides a castable, which is composed of the following raw materials in parts by weight: 8 parts of magnesium oxide, 60 parts of a mixture of nano hollow cage-like carbon microspheres and silicon carbide, 7 parts of nano boron nitride, 2 parts of nano titanium dioxide, 15 parts of nano boron carbide, 8 parts of zirconium oxide, 0.7 parts of cesium garnet powder, 0.6 parts of lanthanum oxide, 0.6 parts of aluminate cement, and 0.2 parts of sodium tripolyphosphate, wherein the content of aluminum oxide in the aluminate cement is 60wt%, and the mass ratio of nano hollow cage-like carbon microspheres to silicon carbide in the mixture of nano hollow cage-like carbon microspheres and silicon carbide is 1:1.
[0033] The specific preparation method of the castable in Comparative Example 2 is consistent with that in Example 1.
[0034] Comparative Example 3 Comparative Example 3 provides a casting material, which is different from Example 1 in that there are differences in the preparation process of the modified nano hollow cage-like carbon microspheres obtained in Preparation Example 1. Specifically, this comparative example uses ordinary carbon powder instead of nano hollow cage-like carbon microspheres to participate in the subsequent preparation process, and the preparation conditions are the same as those in Preparation Example 1.
[0035] The specific preparation method of the castable in Comparative Example 3 is consistent with that in Example 1.
[0036] Comparative Example 4 Comparative Example 4 provides a castable, which is composed of the following raw materials in parts by weight: 8 parts of magnesium oxide, 60 parts of modified nano hollow cage carbon microspheres obtained in Preparation Example 1, 7 parts of nano boron nitride, 2 parts of nano titanium dioxide, 15 parts of nano boron carbide, 8 parts of zirconium oxide, 0.6 parts of lanthanum oxide, 0.6 parts of aluminate cement, and 0.2 parts of sodium tripolyphosphate, wherein the content of alumina in the aluminate cement is 60wt%.
[0037] The specific preparation method of the castable in Comparative Example 4 is consistent with that in Example 1.
[0038] Performance Testing The properties of the castables in Examples 1-3 of the present invention and Comparative Examples 1-4 were tested, and the test results are shown in Table 1.
[0039] Testing standards: compressive strength refers to GB / T 5072-2023, flexural strength refers to GB / T 3001-2017, linear change rate refers to GB / T 5988-2022.
[0040] It can be seen from Table 1 that the refractory castables of Examples 1-3 of the present invention have excellent high temperature stability, thermal shock resistance and mechanical strength.
[0041] Compared with Examples 1-3, the high temperature stability and thermal shock stability of the castables of Comparative Examples 1-3 are significantly reduced. It is analyzed that Comparative Example 1 uses nano hollow cage-like carbon microspheres instead of modified nano hollow cage-like carbon microspheres; Comparative Example 2 uses nano hollow cage-like carbon microspheres and silicon carbide instead of modified nano hollow cage-like carbon microspheres; Comparative Example 3 uses carbon powder instead of nano hollow cage-like carbon microspheres. Further analysis shows that the present invention uses silicon micropowder, diatomaceous earth, and calcium stearate to modify the nano hollow cage-like carbon microspheres. After the modification, the thermal conductivity of the nano hollow cage-like carbon microspheres is further enhanced, thereby improving the high temperature stability of the castable; furthermore, the pore structure of the nano hollow cage-like carbon microspheres is improved after the modification, and has excellent toughness, which can absorb and release the stress at the crack tip when the temperature changes, which helps to reduce the material cracking caused by thermal stress concentration, thereby improving the thermal shock stability of the refractory castable. In addition, silicon carbide is formed on the surface of the nano hollow cage-like carbon microspheres during the calcination process, further improving the high temperature stability and overall thermal shock resistance of the refractory castable.
[0042] Compared with Examples 1-3, the mechanical strength of the castables of Comparative Examples 1-4 is reduced. Analysis shows that none of Comparative Examples 1-3 uses the modified hollow cage-like carbon microspheres of the present invention, and Comparative Example 4 omits the cesium garnet powder. The above results show that the cesium garnet powder itself has a strong hardness, and its synergistic effect with the modified carbon microspheres further improves the mechanical strength of the refractory castable.
[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.
Claims
1. A novel nano-coated refractory castable, characterized in that: The following raw materials are included in parts by weight: 5-10 parts of magnesium oxide, 50-70 parts of modified nano hollow cage carbon microspheres, 5-10 parts of nano boron nitride, 1-3 parts of nano titanium dioxide, 10-20 parts of nano boron carbide, 5-10 parts of zirconium oxide, 0.5-1 parts of cesium garnet powder, 0.5-1 parts of lanthanum oxide, 0.5-1 parts of binder, and 0.1-0.3 parts of water reducer; The preparation process of the modified nano hollow cage-like carbon microspheres is as follows: The nano hollow cage-like carbon microspheres, silicon powder, diatomaceous earth, calcium stearate and water are uniformly mixed and granulated, and the modified hollow cage-like carbon microspheres are obtained after drying and calcining.
2. The novel nano-coated refractory castable according to claim 1, characterized in that: The mass ratio of the nano hollow cage carbon microspheres, silicon powder, diatomaceous earth, calcium stearate and water is 1:(2-4):(1-3):(0.5-1.5):(12-18).
3. The novel nano-coated refractory castable according to claim 1, characterized in that: The drying temperature is 55-65° C., and the drying time is 20-22 hours.
4. The novel nano-coated refractory castable according to claim 1, characterized in that: The calcination temperature is 900-1000° C., and the calcination time is 25-35 minutes.
5. The novel nano-coated refractory castable according to claim 1, characterized in that: The particle size of the cesium garnet powder is 50-70 μm.
6. The novel nano-coated refractory castable according to claim 1, characterized in that: The binder is aluminate cement, and the water reducing agent is sodium tripolyphosphate.
7. The novel nano-coated refractory castable according to claim 6, characterized in that: The content of aluminum oxide in the aluminate cement is 50-80wt%.
8. The novel nano-coated refractory castable according to claim 1, characterized in that: The particle size of the nano boron nitride is 20-40nm, the particle size of the nano titanium dioxide is 50-100nm, and the particle size of the nano boron carbide is 30-50nm.
9. The method for preparing the novel nano-coated refractory castable according to any one of claims 1 to 8, characterized in that: The following steps are involved: Weigh each raw material according to the weight ratio and mix them evenly.
Citation Information
Patent Citations
Refractory castable for kilneye and kiln head cover of rotary kiln
CN102674859A
High CaO content low-consumption magnesite-calcium refractory material casting material and preparation method thereof
CN107235739A
Preparation method and applications of coal asphalt-based lithium ion battery anode material
CN109422258A
Surfacing flux-cored wire of wear-resistant surfacing layer adapting to complex working conditions
CN112025135A
Heat-insulating refractory castable and preparation method thereof
CN118324499A